Desigualdades na acessibilidade ao mercado de trabalho na cidade do Rio de Janeiro - Carneiro, Mariana Souza (2019)
This research explores the relationship between public transport and job distribution throughout the city, trying to understand the effects of public transportation in people’s access to opportunities and how these opportunities are accessed in different areas of the city, based on their spatial and socioeconomic differences. In this context, a methodological procedure is structured, based on the concepts of accessibility and equity, applying the cumulative opportunity measure to evaluate accessibility, and then, the concentration curve is used to assist in the analysis of accessibility inequalities. The city of Rio de Janeiro is analyzed using public transport data from 2018 and formal employment in 2016. The results show an unequal distribution of accessibility, in which the farthest regions from the urban center have less accessibility, due the high concentration of jobs in the city center and the great distances between the city center and peripheral areas. Based on an estimate of average speed, the results show that the public transportation system helps to reduce inequality in job accessibility, between the lower income groups and the ones living farther from the center than to those with higher income and living closer to the center, when compared: the number of jobs located within a certain radius of a neighborhood, with the number of jobs available at an equivalent interval of time.